Family Economic Status and Pupils' Academic Performance in Primary Schools of Kamuganguzi Sub-County Kabale District. - Twinomuhangi, Alex (Kabale University, 2024)
The study was intended to find out the impact of family economic status on pupils' academic performance. The study specifically was meant to find out the causes of low levels of pupils' academic performance and the impact of family economic status on pupils' academic performance. The descriptive cross-sectional survey research design was used for the study where both quantitative and qualitative techniques were used in the data collection process, analysis, presentation, and discussion of findings. Data was collected from six pre-primary schools which were selected using simple random sampling. In those schools, semi-structured questionnaires were administered to head teachers and teachers. It was concluded from the study that limited scholastic materials, pupils' absenteeism, and lack of remedial lessons and preparations were the major causes of low levels of pupils' academic performance. It was also established that family economic background had a significant impact on pupils' academic performance. The study recommended that providing scholastic materials, learning, and instructional materials, attending remedial lessons, feeding pupils on a balanced diet, employing trained teachers, and educating parents during parent's teachers' association meetings on income-generating activities to improve their income levels would effectively improve pupils' level of academic performance.